Politeness Theories in Synge's Riders to the Sea - نغم علي حسن (College of Education for Women, 2019)
This research tackles the play of Synge "Rider to the Sea" to find out whether the theories of Leech (1983) and Brown and Levinson (1987) can be applied or not to this study. The model of Leech (1983) consists of seven principles and for Brown and Levinson (1987),it consists of two principles of politeness where one of them is positive and the other is negative politeness. It is hypothesed that: 1. There is a relation between the two theories. 2. Synge deals with these theories in such a way to depict his characters. 3. It is also hypothesed that every character deals with these principles in such a way to show the events of the play. The study concludes that there is a relation between the two theories in depicting the characters then it shows the misery of life in the island throughout the language of the characters.